Effect of post-exercise sauna bathing on the endurance performance of competitive male runners - Scoon, G. S. M.; Hopkins, W. G.; Mayhew, S.; Cotter, J. D. (Journal of Science and Medicine in Sport, 2007)
The physiological adaptations to sauna bathing could enhance endurance performance. We have therefore performed a cross-over study in which six male distance runners completed 3 wk of post-training sauna bathing and 3 wk of control training, with a 3 wk washout. During the sauna period, subjects sat in a humid sauna at 89.9 ± 2.0 °C (mean ± standard deviation) immediately post-exercise for 31 ± 5 min on 12.7 ± 2.1 occasions. The performance test was a not, vert, similar15 min treadmill run to exhaustion at the runner's current best speed over 5 km. The test was performed on the 1st and 2nd day following completion of the sauna and control periods, and the times were averaged. Plasma, red-cell and total blood volume were measured via Evans blue dye dilution immediately prior to the first run to exhaustion for each period. Relative to control, sauna bathing increased run time to exhaustion by 32% (90% confidence limits 21-43%), which is equivalent to an enhancement of not, vert, similar1.9% (1.3-2.4%) in an endurance time trial. Plasma and red-cell volumes increased by 7.1% (5.6-8.7%) and 3.5% (-0.8% to 8.1%) respectively, after sauna relative to control. Change in performance had high correlations with change in plasma volume (0.96, 0.76-0.99) and total blood volume (0.94, 0.66-0.99), but the correlation with change in red cell volume was unclear (0.48, -0.40 to 0.90). We conclude that 3 wk of post-exercise sauna bathing produced a worthwhile enhancement of endurance running performance, probably by increasing blood volume.